Meningkatkan Hasil Belajar Operasi Hitung Perkalian Menggunakan Metode Permainan Kartu Bilangan Pada Siswa Kelas III SD Negeri Pabelan 2 - Udayana, Yusuf (Universitas Sebelas Maret, 2020)
Class action research was motivated by the discovery of cases of third grade students at SD Negeri Pabelan 2, it was identified that in learning mathematics, multiplication arithmetic operations were still low. This fact is shown through the value of the Minimum Completeness Criteria (KKM) for Mathematics, which is 75, only 36% of students achieve the KKM score. The purpose of the research is to improve the achievement of mathematics learning outcomes with the number card game method. This study used a classroom action research design consisting of two cycles. Data collection techniques in this study through written tests and observations. From the results of the study showed that the mastery of learning increased in the first cycle by 68% and in the second cycle by 72%. From these results it can be concluded that by applying the number card game method, multiplication and division counting operations material can improve mathematics learning outcomes and provide a fun learning atmosphere and can motivate students to be active in learning.